(untitled) (Research, Society and Development, 2023)
The following article focuses on the use of hydrogels in 3D skin printing as an alternative method to experimenting with cosmetic products on animals. It will review all aspects and concepts related to 3D skin bioprinting, from the concept of skin, creation of the 3D model, biomaterials used and their suitability, highlighting the hydrogel, types of cells and their functions, real bioprinting technologies, together with the challenges and future prospects, satisfying clinical and industrial needs. Objective: To analyze the applications, challenges and trends of hydrogel in 3D skin printing within the cosmetics industry. Method: This study is a literature review, in which data was collected from a specific area of knowledge, with the aim of analyzing the use of hydrogel in 3D skin printing, as well as its challenges and future trends. Conclusion: 3D bioprinting is a promising technology that can achieve the rapid and reliable production of biomimetic cellular skin substitutes, satisfying clinical and industrial needs.